PUSTAKAWAN PERPUSTAKAAN PERGURUAN TINGGI ISLAM MENGHADAPI ERA MILENIAL - Rodin, Rhoni; Junaidi, Heri; Mubarokah, Adzkiyah (UPT. Perpustakaan Universitas Muhammadiyah Ponorogo, 2024)
The aim of this research is to analyze how librarian of Islamic Higher Education Libraries faces the millennium era. This research uses a qualitative approach, with literature review techniques. A literature review is a survey of scientific articles, books, and other sources relevant to a particular problem, area of research, or theory, and in so doing, provides a description, summary, and evaluation of various works. The results of the research show that human resource management of Islamic higher education libraries facing the millennial era really needs to be done by implementing a sustainable pattern of human resource development regarding knowledge and skills in the fields of libraries and information technology. There are several issues that must be of primary concern, namely: 1) The need for education for library technicians (functional professional skills/librarian assistants), and libraries (functional skills/librarians); 2) Development of the librarian profession by attending seminars, scientific discussions, workshops, writing papers, and the like; 3) Mastery of information technology; 4) Shift in values and work ethic caused by changes in mindset; 5) Making librarians aware of the importance of roles and functions in the information era to realize the achievement of an information society; and 6) Transition of conventional library management to electronic libraries. Therefore, library Human Resources (HR) in the millennial era face various changes and challenges, there are several characteristics that library HR must have, namely: 1) Digital Literacy; 2) Adaptability; 3) Customer Service; 4) Collaboration; 5) Continuous Education; 6) Creativity and Innovation; 7) Understanding Diversity Needs; and 8) Leadership